Diseño de un sistema de control de inventarios en la empresa surticarnes express s.a.s en el municipio de ciénaga. (2024)
The objective of the work was to design an inventory control system for the Surticarnes Express supermarket. The Pareto Diagram technique was used to organize the products into ABC categories based on their contribution to total sales. Category A products represent approximately 80% of total sales, category B products about 15%, and category C products about 5%. These classifications were then combined with those of XYZ to obtain an ABC-XYZ classification, which provides a more complete view of the behavior of the products in terms of sales and stability in demand. It has been decided to manage high demand and high variability products, such as those classified as AZ, through a continuous inventory review system. For the other products, a periodic inventory review system will be used, since their demand does not vary so much. In addition, an ordering cost of $1000 and a maintenance cost of $1 per year were established, considering that with an ordering cost of $1 the units to be shipped were very limited.